The effect of nutritional education program on quality of life and serum electrolytes levels in hemodialysis patients: A single-blind randomized controlled trial. Issue 9 (September 2020) - Naseri-Salahshour, Vahid; Sajadi, Mahbobeh; Nikbakht-Nasrabadi, Alireza; Davodabady, Fahimeh; Fournier, Andrew
Highlights: Nutrition education improves patient quality of life scores. Nutrition education increases patient knowledge and skills. Nutrition education can be expedited through the use of a Messenger application. Abstract: Objective: To determine the effect of nutrition education program on hemodialysis patients' quality of life (QoL) and serum electrolytes levels. Methods: This study was a randomized controlled trial in which 94 eligible hemodialysis patients were randomly assigned to intervention (n = 48) and control (n = 46) groups. In the intervention group, the patients were trained in healthy nutrition for four weeks. After two months, samples of both groups completed the Kidney Disease Quality of Life Instrument (KDQOL) and Na, K, P, Ca and Mg levels were also measured and compared. Results: There were no significant differences in QoL scores and electrolytes between the two groups before intervention (p > 0.05). After intervention the QoL scores in the intervention group were significantly higher than in the control group (p < 0.05). However, after intervention the levels of Na, K, P and Mg in the intervention group were significantly lower than in the control group (p < 0.05). Calcium level was not significantly different between the two groups after intervention (p = 0.16). Conclusion: The results showed that e-learning is effective in improving the QoL and serum electrolytes of hemodialysis patients. Practice Implications: This paper could serve as support for clinical healthcare professionals to improve patient knowledge and QoL through virtual education methods.